Necesidad de sancionar y tipificar en el código orgánico integral penal, la figura delictiva del porte de armas blancas en espacios públicos - Maldonado Celi, Luis Miguel (2022)
This thesis entitled "NEED TO SANCTION AND CLASSIFY IN THE INTEGRAL ORGANIC CRIMINAL CODE, THE CARRYING OF CUTTING WEAPONS IN PUBLIC SPACES", refers to the importance of punishing the person who carries cutting weapons in public spaces, because It is common day by day to hear in our environment, on the various television channels, radios, newspapers, so many bloody acts and crimes that are carried out on public roads due to the misuse and possession of these instruments, and it is that it is necessary to do allusion to how important it is to create regulations in our country that allow punishing those who carry these objects and thereby empower the National Police to carry out the arrest of the individual, since in the majority of operations carried out in our country for control and security according to several reports, there are countless bladed weapons in the possession of the person, but since there is no regulation that sanctions, only the weapon is removed According to these aspects raised, it is where the importance of sanctioning and criminalizing in our comprehensive organic criminal code the criminal figure of carrying bladed weapons in public spaces is reflected in order to counteract so many incidents caused by those instruments and thus guarantee security. public, the peaceful and harmonious welfare of the community as mandated by our Constitution of the Republic of Ecuador 2008. Likewise, materials and methods were applied to develop the present investigation, conduct interviews and surveys, which served to help propose a reform project to the Organic Comprehensive Criminal Code, Chapter VI, reference to crimes against Public Security, including the figure offense mentioned above and its respective sanction.